РАЗВИТИЕ КОГНИТИВНЫХ ЭЛЕМЕНТОВ ЦЕННОСТЕЙ В СИСТЕМЕ ОБРАЗОВАНИЯ - Абдурахманова, А.Т. (SCIENCE and SOCIETY, 2022)
On this basis, the Educational concept underlying value education advocates strengthening the connection between the acquisition of broad and deep knowledge in the fields of knowledge and the education of values, morality and virtue.
Keywords: education; conception; graduate; knowledge; value